Universal Design for Learning: University Faculty Stages of Concerns and Levels of Use - Diana J. LaRocco; Danielle S. Wilken (Arizona State University, 2013)
Increasingly, students with disabilities are attending postsecondary schools.  As with any form of diversity, there are also pedagogical challenges and opportunities that go beyond accommodation and support the goal of learning for all.  This paper describes the results of the data collection phase of a faculty action-research project that grew from a core group of university faculty members' concerns about how best to support students with disabilities on campus.  A researcher-developed survey was used to identify faculty members' stages of concern about and use of nine Universal Design for Learning guidelines in their classes.  Findings reveal that the 46 respondents were at the stage of being largely concerned with learning more about the nine guidelines.  The results provide a snapshot of initial stages of concern.  Recommendations for action are provided.